Revision of Prophorostoma Townsend, 1927 (Diptera, Tachinidae, Dexiinae), with the description of a new species - Nihei, Silvio Shigueo; Pansonato, Marcelo Petratti (Papéis Avulsos de Zoologia, 2006)
Revision of Prophorostoma Townsend, 1927 (Diptera, Tachinidae, Dexiinae), with the description of a new species. The Neotropical dexiine genus Prophorostoma Townsend, 1927 is revised; the type species Prophorostoma pulchra Townsend, 1927 is redescribed; and a new species (Prophorostoma tomjobimi Nihei) is described from the state of Rio de Janeiro, Brazil.